Flaunting it! : a decade of gay jounalism from The Body Politic. - Jackson, Edward; Persky, Stan (Vancouver Toronto : New Star Books Ltd Pink Triangle Press, 1982)
Fonds Suzan Daniel (FSD)
Engels
Monografie